Does the Discovery Learning Model Based on Local Wisdom Improve Students' Critical Thinking Skills in Chemistry Learning? Meta-Analysis - Elisabeth Temuji Koten; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2024)
The industrial revolution 4.0 has a positive influence on students' critical thinking skills through the discovery learning model. However, whether the discovery learning model based on local wisdom can improve students' critical thinking skills in chemistry learning that does not yet have a uniform conclusion. This study aims to determine whether the discovery learning model based on local wisdom can improve students' critical thinking skills in chemistry learning. This type of research is a meta-analysis. Data was collected through ScienceDirect, Speinger Journal, Researchgate, Mendeley and ERIC. The data entered must meet the eligibility criteria, namely Research must be experimental or quasi-experimental, research comes from SINTA and Scopus indexed journals, Research related to discovery learning models based on local wisdom on students' critical thinking skills in chemistry learning, Research published in 2020-2024, research has complete data to calculate effect size values, and sample size (N) ≥ 25 students. Statistical analysis with the help of JASP. The results of the analysis of 24 studies explained From this meta-analysis research, it can be concluded that there is a significant influence of discovery learing models based on local wisdom on students' critical thinking skills (z = 11.44; p < 0.001). This effect is included in the very high criterion (rRE = 1.291). These findings explain that the discovery learning model based on local wisdom is effective in improving students' critical thinking skills in science learning with a CI of 95% ([1.06; 1.51).